2009
DOI: 10.1117/1.3078811
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative detection of single submicron and nanoparticles in human skin by scanning transmission x-ray microscopy

Abstract: First results on single particle detection in human skin samples by x-ray microscopy are reported. 94+/-6 and 161+/-13 nm gold core particles with silica shells and 298+/-11 nm silica particles coated with a gold shell on ultramicrotome sections of human skin were determined. The particles were applied on fresh intact skin samples, which were sectioned prior to imaging. After screening the sections by conventional microscopy techniques, defined areas of interest were qualitatively investigated by scanning tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 59 publications
3
38
0
Order By: Relevance
“…These results indicated the possibility of using any of the markers for the shortterm skin permeation experiments. Similar results have been observed in previous reports for polymeric nanoparticles with fluorescent markers (Abdel-Mottaleb et al, 2011;AlvarezRoman et al, 2004;Graf et al, 2009). The same was observed for QDs when their penetration was tested in intact rat skin and in flexed, tape stripped (30 times) and abraded skin (using sandpaper 60 times to remove the stratum corneum) in a flow through cells.…”
Section: Discussionsupporting
confidence: 88%
“…These results indicated the possibility of using any of the markers for the shortterm skin permeation experiments. Similar results have been observed in previous reports for polymeric nanoparticles with fluorescent markers (Abdel-Mottaleb et al, 2011;AlvarezRoman et al, 2004;Graf et al, 2009). The same was observed for QDs when their penetration was tested in intact rat skin and in flexed, tape stripped (30 times) and abraded skin (using sandpaper 60 times to remove the stratum corneum) in a flow through cells.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, Graf et al found that gold particles with dimensions of 161±13 nm were able to penetrate the superficial layers of the SC and hair follicles. 34 Also in the study by Graf et al, no deeper penetration was observed. 34 It was noted in the present study that silver-containing aggregates …”
Section: Notesmentioning
confidence: 94%
“…34 Also in the study by Graf et al, no deeper penetration was observed. 34 It was noted in the present study that silver-containing aggregates …”
Section: Notesmentioning
confidence: 94%
“…This calculation was based on the assumption that formation of a protein corona around NDs resembles a classical ligand binding model and thus follows the law 59 Soft X-rays also provide spatial resolution of 25-30 nm 60 and spectral resolution on the order of 100 meV 61,62 that can differentiate between classes of biomolecules and can identify NPs as therapeutic carriers in cells and tissues. 57 The spectrum of lys-NDs (red; Figure 3A) recorded as a reference shows identifiable peaks at 288.2 eV, 292.5 eV, and 297.5 eV, indicated by arrows, which are absent in the spectrum of intracellular proteins (green; Figure 3A) obtained from the untreated cells. For detailed evaluation, untreated cells and lys-ND-treated cells were scanned separately through STXM at wide range of photon energies.…”
Section: Scanning Transmission X-ray Microscopymentioning
confidence: 99%
“…It allows high-resolution imaging that enables evaluation of interactions on the level of individual particles. [56][57][58] Most importantly, it can be applied to fully hydrated biological materials, which allows functional analysis of molecular mechanisms in a living cell under zeta potential as a function of incubation time with FBS. Upon visual inspection, the lys-NDs showed no visible sedimentation up to 3 days ( Figure 2C), indicating good dispersibility.…”
Section: Scanning Transmission X-ray Microscopymentioning
confidence: 99%